Impact of elevated aspartate and alanine aminotransferase on metabolic syndrome and its components among adult people living in Ningxia, China - Kun-Peng He (KeAi Communications Co., Ltd., 2015)
Objective: Metabolic syndrome (MS) is a combination of medical disorders that increase the risk for cardiovascular disease and diabetes mellitus. It suggests an association between an elevated serum aminotransferase level and MS. Little data show the relationship between the levels of serum aminotransferase and the incidence of MS in Ningxia, China. Methods: A total of 5415 subjects who received medical health checkups from 2007 to 2009 were enrolled in the study. The participants were interviewed by trained health workers under a structured questionnaire. MS was defined according to the modified ATPIII criteria for Asian Americans by the American Heart Association (AHA-ATP III). Results: The prevalence of elevated aspartate aminotransferase (AST) and ALT (>40Â U/L) were 7.1% and 22.2% in males, and 2.1% and 4.8% in females respectively. The prevalence of MS was 32.1% in males and 15.4% in females. The components of MS were significantly more in the group with elevated aminotransferase levels than in the group with normal aminotransferase levels. The odds ratios (95% CI) for elevated AST were 1.90 (1.49, 2.42), 2.59 (2.01, 3.39), 1.68 (1.32, 2.15), and 1.81 (1.36, 2.42) in the adults with abdominal obesity, high serum triglycerides levels, high blood pressure, and high plasma glucose levels respectively. After adjustment for age, the odds ratios (95% CI) for elevated ALT were 3.08 (2.63, 3.61), 4.30 (3.64, 5.08), 1.26 (1.08, 1.48), 2.16 (1.93, 2.65) and 2.38 (1.96, 2.87) in adults with abdominal obesity, high serum triglycerides levels, low serum high-density lipoproteincholesterol (HDL-C), high blood pressure, and high plasma glucose levels respectively. The odds ratios (95% CI) for elevated AST were 1.67 (1.06, 2.63), 2.28 (1.46, 3.63), 2.59 (1.59, 4.21) and for elevated ALT 2.02 (1.50, 2.73), 2.68 (1.96, 3.65), 3.94 (2.86, 5.43) for the subjects with 1, 2, and â¥3 risk factors after adjustment for age, gender, and BMI. Conclusion: The serum aminotransferase levels were higher in males compared to females, and serum ALT level was more closely associated with MS than the AST level in adults in Ningxia, China. With an increasing the number of components of MS, the aminotransferase levels and the risks for elevated aminotransferase increase, whereas the AST/ALT ratios decrease. Keywords: Metabolic syndrome, Serum aminotransferase, Odds ratios